2013
DOI: 10.1002/14651858.cd006764.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Different corticosteroids and regimens for accelerating fetal lung maturation for women at risk of preterm birth

Abstract: It remains unclear whether one corticosteroid (or one particular regimen) has advantages over another.Dexamethasone may have some benefits compared with betamethasone such as less IVH, and a shorter length of stay in the NICU. The intramuscular route may have advantages over the oral route for dexamethasone, as identified in one small trial. Apart from the suggestion that 12-hour dosing may be as effective as 24-hour dosing of betamethasone based on one small trial, few other conclusions about optimal antenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(201 citation statements)
references
References 54 publications
1
184
0
16
Order By: Relevance
“…Although dexamethasone is characterized by a greater affinity to glucocorticoid receptors, betamethasone has a longer half-life [120]. Betamethasone is superior for the prevention of RDS in comparison to dexamethasone; but not for reduction of intraventricular hemorrhage [121]. The combined use of these two corticosteroids has not been tested.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Although dexamethasone is characterized by a greater affinity to glucocorticoid receptors, betamethasone has a longer half-life [120]. Betamethasone is superior for the prevention of RDS in comparison to dexamethasone; but not for reduction of intraventricular hemorrhage [121]. The combined use of these two corticosteroids has not been tested.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Namely, the Cochrane Collaboration in 2006, 9 which was an extensive document to assess the effects of maternal antenatal corticosteroids on the mother, the fetus, the neonate, and the child; the Cochrane Collaboration in 2007, 10 which evaluated the effectiveness and safety of repeat courses of corticosteorids; and the Cochrane Collaboration in 2008, 11 which elaborated on the effects of various types and dosing regimens of corticosteroids.…”
Section: Antenatal Corticosteroidsmentioning
confidence: 99%
“…168 A later systematic review found reduced risk for combined serious outcome including NEC, with repeat doses of antenatal steroids compared to a single dose, 169 and a meta-analysis from 2013 found no significant difference between sorts of corticosteroids, ways of administration or regimen, although with just one or two studies addressing each outcome. 170 ➢ Caesarean section. Given the importance of colonisation with normal intestinal flora for the maturation of the neonatal intestine, caesarean section might be expected to increase the risk for NEC.…”
Section: Pathophysiologymentioning
confidence: 99%